2000
DOI: 10.2307/177214
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variation in Fish Assemblages across a Beaver-Influenced Successional Landscape

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Ecological Society of America is collaborating with JSTOR to digitize, preserve and extend access to Ecology.Abstract. Beavers are increasingly viewed as "ecological engineers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 14 publications
(28 reference statements)
0
31
0
Order By: Relevance
“…, Snodgrass & Meffe , Smith & Mather ). Temporal heterogeneity is also created due to the creation and abandonment of beaver impoundments, and the differing effects of beaver ponds of different ages; this has further positive impacts on fish biodiversity (Schlosser & Kallemeyn ). Restoring degraded watercourses through impoundment and increasing the abundance of dead wood also increases total fish biomass present within a stream reach (Acuna et al.…”
Section: Review Of the Impacts Of Beavers On Biodiversitymentioning
confidence: 99%
“…, Snodgrass & Meffe , Smith & Mather ). Temporal heterogeneity is also created due to the creation and abandonment of beaver impoundments, and the differing effects of beaver ponds of different ages; this has further positive impacts on fish biodiversity (Schlosser & Kallemeyn ). Restoring degraded watercourses through impoundment and increasing the abundance of dead wood also increases total fish biomass present within a stream reach (Acuna et al.…”
Section: Review Of the Impacts Of Beavers On Biodiversitymentioning
confidence: 99%
“…It seems likely that longevity of beaver ponds may affect their ecological function, and several studies have demonstrated that fish assemblage in beaver pond habitats varies with pond age (Snodgrass & Meffe 1998;Schlosser & Kallemeyn 2000). We found that beaver dams were generally larger and more abundant in the upper mainstem than in the tributaries, and mainstem ponds appeared older and more complex.…”
Section: Contrasting Mainstem and Tributary Habitatsmentioning
confidence: 52%
“…Previous research has shown that beaver pond habitat can have substantial consequences for stream fish populations: individual species, particularly salmonids, have shown higher growth, survival or abundance within beaver ponds relative to unimpounded stream habitat (Murphy et al 1989), and some species preferentially select beaver pond habitats during certain life stages or environmental conditions (e.g., Schlosser 1995). Beaver ponds can influence composition of fish assemblages at scales ranging from individual ponds (Snodgrass & Meffe 1999) to entire drainages (Schlosser & Kallemeyn 2000). Beaver ponds can influence composition of fish assemblages at scales ranging from individual ponds (Snodgrass & Meffe 1999) to entire drainages (Schlosser & Kallemeyn 2000).…”
Section: Introductionmentioning
confidence: 99%
“…This process is then reversed with the failure of beaver dams (Andersen and Shafroth, 2010). The spatial and temporal mosaic of beaver-dam construction and destruction is evident in beaver-impacted landscapes and has been found to be important in describing both fish abundance and species richness (Schlosser and Kallemeyn, 2000). On a regulated river in the Sonoran Desert, Andersen and Shafroth (2010) found that the ratio of lentic:lotic habitat along a 58-km river fell from 19:1 to o3:1 after 7 years of favorable flows.…”
Section: Beavers and Channel Slopementioning
confidence: 99%